Outlooks / Through Literature - Cage Thomas E; Farrell Edmund James; Pforddresher John; Rodrigues Raymond J (Scott, Foresman And Company, 1976)
Twelve Angry Men, An Enemy of the People, The Short Story, Poetry, Julius Caesar, Prose Forms, Medieval Tales and Legends, Three One-Act Olays.
Twelve Angry Men, An Enemy of the People, The Short Story, Poetry, Julius Caesar, Prose Forms, Medieval Tales and Legends, Three One-Act Olays.